"Closer‐to‐home" strategy benefits juvenile survival in a long‐distance migratory bird. Issue 16 (23rd July 2019) - Cheng, Yachang; Fiedler, Wolfgang; Wikelski, Martin; Flack, Andrea
Abstract: Human‐induced changes in the climate and environment that occur at an unprecedented speed are challenging the existence of migratory species. Faced with these new challenges, species with diverse and flexible migratory behaviors may suffer less from population decline, as they may be better at responding to these changes by altering their migratory behavior. At the individual level, variations in migratory behavior may lead to differences in fitness and subsequently influence the population's demographic dynamics. Using lifetime GPS bio‐logging data from 169 white storks ( Ciconia ciconia ), we explore whether the recently shortened migration distance of storks affects their survival during different stages of their juvenile life. We also explore how other variations in migratory decisions (i.e., time, destination), movement activity (measured using overall body dynamic acceleration), and early life conditions influence juvenile survival. We observed that their first autumn migration was the riskiest period for juvenile white storks. Individuals that migrated shorter distances and fledged earlier experienced lower mortality risks. In addition, higher movement activity and overwintering "closer‐to‐home" (with 84.21% of the tracked individuals stayed Europe or North Africa) were associated with higher survival. Our study shows how avian migrants can change life history decisions over only a few decades, and thus it helps us to understand and predict how migrants respond to the rapidly changing world. Abstract : Using bio‐logging data from a long‐distance migratory species, the white stork ( Ciconia ciconia ), we found that the individuals with shortened migration distance and those that overwintered in Europe and North Africa had higher survival probability during the juvenile stage, the riskiest life period for many migrants. In addition, higher movement activity and early fledging were associated with higher survival. Our study shows how avian migrants can adjust life history decisions linked to fitness over few decades.